QUALITY OF WORK LIFE PADA ANGGOTA PARTAI POLITIK - Geris, Pradhana Anindhiya (2014)
Geris PradhanaAnindhiya (0901194).Quality of Work Life padaAnggotaPartaiPolitik. Skripsi. Jurusan Psikologi Universitas Pendidikan Indonesia. Bandung 2014.Penelitian ini bertujuan untuk mengetahuigambaranatasQuality of work Life (KualitasKehidupanKerja) padaorganisasipartaipolitikdanfaktor-faktorapasaja yang ikutmempengaruhinya. Metode yang digunakan adalah metode penelitian kualitatif dengan model penelitian studi eksploratif. Teknik pemilihan subjek yang digunakan adalah teknik purposive sampling. Pengumpulan data yang dilakukan dengan cara wawancara dan semi terstruktur. Hasil penelitian ini didapatibahwaadafaktor yang mempengaruhikualitaskehidupankerjaanggotapartaipolitik di organisasinyayaitusebagaiberikut: 1). Hubunganantarindividu 2).Otonomi 3).Penguasaanlingkungan 4).Kesamaannilaidenganideologipartai 5).TujuanHidup. Lima factor inimasukkedalam factor intern.Selainkelimafaktor intern, terdapatduafaktorekstern yang mempengaruhiKualitasKehidupanKerjapadaanggotaPartaiPolitik. Faktoreksterntersebutantara lain: 1. SistemKelembagaanPartai 2). TokohPemimpinPartai. Organisasipartaipolitik di Indonesia perlumemperhatikankualitaskehidupankerjadarisumberdayamanusianya.Organisasipartaipolitikperlumemperhatikan factor-faktor yang munculdarihasilpenelitianiniuntukkemudiandijadikanbahanacuandalampengukurankualitaskehidupankerjasumberdayamanusia di organisasipartaipolitiknya. Geris Pradhana Anindhiya (0901194). Quality of Work Life in the Political Party Members. Research Paper.Psychology.Department of Psychology Indonesia University of Education. Bandung 2014. This research aimed to find a picture of the Quality of work Life (Quality Work Life) on the organization of political parties and what factors influence that participate. The method which is used in this research is qualitative method with exploratory study model. Subject selection technique used was purposive sampling technique. Data collection is done by means of semi-structured interviews. The results of this study found that there are factors that affect the Quality of Work Life in the organization of political party members are as follows : 1). The relationship between individuals 2). Autonomy 3). Environmental mastery4). The similarity values with the ideology of the party 5). Purpose of Life. These five factors enter into the internal factor. In addition to the five internal factors, there are two external factors that affect the Quality of the Work Life Political Party member. The external factors include: 1). Institutional Party System 2). Party leader figures. Organization of political parties in Indonesia need to pay attention to the quality of work life of its human resources. Organization of political parties also need to pay attention to the factors that emerged from this research to then be used as a reference in measuring the quality of work life of human resources in the organization of political parties.